Understanding and managing cardiac involvement in systemic sclerosis. (4th March 2023) - Moysidou, Georgia-Savina; Dara, Athanasia; Arvanitaki, Alexandra; Skalkou, Anastasia; Pagkopoulou, Eleni; Daoussis, Dimitris; Kitas, George D; Dimitroulas, Theodoros
ABSTRACT: Introduction: Cardiac involvement is common in systemic sclerosis occurring in up to 80% of patients. Primary myocardial dysfunction results from impairment of coronary microvascular circulation, myocardial inflammation and fibrosis with the prevalence of atherosclerosis remaining contradictory. Areas covered: This review presents the various aspects of cardiac involvement in SSc from a pathophysiological, clinical, diagnostic and therapeutic standpoint. Imaging modalities with emerging role in the understanding of mechanisms and prompt diagnosis of myocardial fibrosis namely cardiac magnetic resonance are also discussed. Expert opinion: Cardiac involvement in SSc – and particularly primary myocardial disease – remains a challenge as clinical symptoms manifest in advanced stages of heart failure and convey poor prognosis. Over the last years the introduction of sophisticated imaging methods of myocardial function has resulted in a better understanding of the underlying pathophysiological processes of myocardial damage such as microvasculopathy, inflammation, diffuse or focal fibrosis. Such developments could contribute to the identification of patients at higher risk for subclinical heart involvement for whom diligent surveillance and prompt initiation of therapy with cardioprotective and/or immunosuppressive drugs coupled with invasive interventions namely radiofrequency ablation, implantable cardioverter-defibrillator when indicated, may improve long-term outcomes.